An Adaptive Architecture for Control of Uncertain Dynamical Systems with Unknown Actuator Bandwidths⁎. Issue 12 (2018) - Gruenwald, Benjamin C.; Yucelen, Tansel; Dogan, K. Merve; Muse, Jonathan A.
Abstract: Closed-loop system stability of adaptive control architectures for autonomous aerospace vehicles can be seriously degraded by the presence of actuator dynamics. To this end, recent research by the authors focuses on a new reference model design approach such that not only closed-loop system stability is rigorously addressed using linear matrix inequalities, but also the proposed reference model achieves better performance characteristics as compared with a well-adopted method in the literature called pseudo-control hedging. Yet, this reference model assumes the exact knowledge of the actuator bandwidth parameter, where such an assumption may not always hold for practical aerospace applications. Motivated from this standpoint, this paper generalizes our recent results such that the exact knowledge of the actuator bandwidth parameter is no longer necessary. Specifically, we utilize an online estimate of the actuator bandwidth parameter in the proposed reference model and show the stability of the closed-loop dynamical system using tools and methods from Lyapunov theory and linear matrix inequalities. An illustrative numerical example involving the short-period dynamics of a hypersonic vehicle model is also included in this paper to elucidate the proposed adaptive architecture for control of uncertain dynamical systems with unknown actuator bandwidths.